Obtenção e caracterização de nanotubos de carbono e avaliação de propriedades térmicas e mecânicas de seus compósitos com o polipropileno - Erick de Souza Ávila (2014)
In this work, polypropylene nanocomposites with carbon nanotubes (CTN) grown directly over amorphous silica powders were studied. In order to obtain the CNTsilica fillers, a three-zone tubular reactor was developed, with an operating capacity for approximately 300g per run. Two inorganic fillers were selected to be used as substrate for the growth of the CNT: MgO/Al2O3 and amorphous silica. Scanning electron microscopy (SEM) analysis confirmed the growth of the CNT anchored in the filler particles and identified some CNTs with large diameters. The concentrations of CNT used for the experiments were: 0.01%, 0.05%, 0.1%, and 0.5% in mass. To characterize the materials and evaluate the performance of the nanocomposites the following techniques were applied: Thermogravimetry (TG), Differential Scanning Calorimetry (DSC), Absorption Spectroscopy in the Infrared region by Fourier Transform, (FTIR), Scanning Electron Microscopy (SEM), and Stress-Strain curves. The addition of silica filler increased the hardness of the polypropylene composites. The modulus values for the composites increased as the concentration of the nanofiller increased, even for low concentrations of CNT. There was not any significant variation on values of yield strength with the addition of the CNT-containing fillers. Nevertheless, a small increase in the breaking strength was observed as the concentration of CNT increased